Ekonomi Kreatif Sebagai Alternatif Prospek Pembangunan Ekonomi di Indonesia - Darwin Hartono (STIE AMKOP, 2023)
The rationale for the emergence of creative industries in developed countries is globalization in the economic sector, thereby increasing the pressure of competition between countries in large-scale conventional industrial sectors such as the manufacturing industry, which has an impact on increasing unemployment rates. In addition, a way is needed to overcome the problem of reducing funds for artistic activities. To overcome these two problems, it is necessary to rebuild large-scale industries. However, in reality it is no longer possible because it is politically unacceptable for large-scale industries to be closely related to environmental pollution and land availability issues. Therefore, light economic activities or weightless economies are developed which can generate large profits but are politically acceptable, such as cafes and theaters which can increase the acquisition of funds for artistic activities. This creative industry and creative economy should be used as an alternative prospect for development in Indonesia. This concept has contributed to several aspects of life, not only from an economic perspective, but can also have a positive impact on other aspects such as enhancing the nation's image and identity, fostering innovation and creativity of the nation's children to use renewable resources. Key Words: Creative Industry, Creative Economic, Economic Development, Indonesia